The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/2017jc013096
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal Ocean Wave Emerged in SAR Image Spectra Under Specific Condition

Abstract: Velocity bunching causes nonlinear modulations in synthetic aperture radar (SAR) images of oceanic scenes. SAR images for the azimuth waves exhibit destructive wavy patterns because of azimuthal distortion caused by velocity bunching. Meanwhile, velocity bunching creates constructive wavy patterns for long waves in certain cases. This paper aims to provide a simple indication for practical interpretation of plausible wavy patterns. A numerical simulation had been performed to address how velocity bunching form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Liu et al [15] suggested a method to simulate the SAR images of ship in different motion states by constructing the mesh model of the vessel, and the hydrodynamic models of the dynamic ship wake and ocean surface. Yoshida et al [16] explained the mechanism of azimuthal ocean wave emerged in SAR image spectra under specific condition based on a numerical simulation. Wang et al [17] proposed a simulation method for oceanic shear-wave-generated eddies, which was employed to research the imaging results of different radar frequencies, look directions of radar, wind speeds, and wind directions.…”
mentioning
confidence: 99%
“…Liu et al [15] suggested a method to simulate the SAR images of ship in different motion states by constructing the mesh model of the vessel, and the hydrodynamic models of the dynamic ship wake and ocean surface. Yoshida et al [16] explained the mechanism of azimuthal ocean wave emerged in SAR image spectra under specific condition based on a numerical simulation. Wang et al [17] proposed a simulation method for oceanic shear-wave-generated eddies, which was employed to research the imaging results of different radar frequencies, look directions of radar, wind speeds, and wind directions.…”
mentioning
confidence: 99%